Controle de plantas de soja voluntárias com herbicidas sulfonilureias - Biedacha, Rodrigo (2018)
With the implantation of the sanitary empty to the soybean culture the cultivation of the bean plantation in succesion soybean has intensied use. Soybean grains continue in the soil after harvest being for dehiscence or harvest losses, show up potential for emerge and turning voluntary plants during the bean crop, causing negative impact in the rendiment. The objective of this study was to determine levels of the controls of twenty soybean genotypes with the herbicides ethoxysulfuron and halosulfuron, the sulfonilureias group registrate for the control the soy bean in the bean plantation. Two experimentes were conducted, one with ethoxysulfuron and one with halosulfuron on both in vegetation house using factorial 20 x 2. The first factor is constituted for twenty cultivars soybean; The second factor for constituted for 3 doses of the herbicide (0, 45 g and 90g ha-1 for ethoxysulfuron) and (0,80g, 160 g ha-1 for halosulfuron). Were determined: (a) tolerance for visual scale at 7,14,21,28 DAA; (b) plants height at 14,28 DAA; (c) green mass and dry mass of aerial pats. Was perfomed a variance analysis of the F test and averages was compared at Skot- Knott test (P<0,05). The soybean genotypes CD 216, BS 2606 ipro, BMX 5953 and 1519 LL was considered more tolerant in comparison with others. as well as ethoxysulfuron or halosulfuron. The cultivars BRS 283, BR 16_5, BR 16_8, , Monsoy 6410, and BRS 284 was more sensitives in comparison with other, as well as ethoxysulfuron or halosulfuron. There was satisfactory control in 16 about 20 soybean genotypes experimented tested. About an overall form, in both herbicides, the double dose not increment significance in the control levels of soybean cultivars evaluted, in comparison whit the control exercised for recommended dose. The variability of the response about soybean genotypes on herbicides ethoxysulfuron and halosulfuron it important information for handling voluntary soybean plants in half of bean plantation joint.